Difficult transitions foreign policy troubles at the outset of presidential power - Campbell, Kurt M. 1957- (Brookings Institution Press, 2008)
"Gives an overview of presidential transitions in foreign policy including case studies of prominent episodes. Pinpoints causes of fiascos--writing off previous administrations? policies and failing to appreciate differences between campaign promises and policy realities. Provides a road map to help new administrations steer clear of the land mines ahead"--Provided by publisher.